Technické systémy v bytovém domě s velmi nízkou energetickou náročností - Pastukhov, Semen; Semen Pastukhov (České vysoké učení technické v Praze, 2022)
Tato diplomová práce se zabývá návrhem systémů vytápění, přípravy teplé vody a větrání pro dům s velmi nízkou energetickou náročností. Teoretická část práce zkoumá závislost ekonomické a energetické účinnosti různých variant technických systémů, lišících se technologií vytápění, průměrným součinitelem prostupu tepla a přítomností FVE, na investičních a provozních nákladech na zateplení obálky budovy a technického zařízení na příkladu novostavby bytového domu v ekonomických a právních podmínkách České republiky v roce 2022.

This thesis deals with the design of heating, hot water preparation and ventilation systems for a house with very low energy consumption. The theoretical part of the thesis investigates the dependence of the economic and energy efficiency of different variants of technical systems, differing in heating technology, average heat transfer coefficient and the presence of PV, on the investment and operating costs of the insulation of the building envelope and technical equipment on the example of a new-build apartment building in the economic and legal conditions of the Czech Republic in 2022.
Technical Systems in the Apartment Building with Very Low Energy Performance
Keywords: vytápění; větrání; bytový dům; pasivní dům; energetická náročnost; heating; ventilation; apartment building; passive house; energy performance